Passover - Marx, David F. (New York : Children's Press, 2001)
An introduction to the traditions and foods of Passover.
Includes index.
1.7
K-3
Keywords: Passover -- Juvenile literature; Passover; Seder; Holidays; Passover; Seder; Jewish holidays